Investigating the influence of intraindividual changes in perceived stress symptoms on injury risk in soccer - Clement, D.; Ivarsson, A.; Tranaeus, U.; Johnson, U.; Stenling, A. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Research has shown that high levels of stress and stress responsivity can increase the risk of injuries. However, most of the research that has supported this notion has focused on between-person relationships, ignoring the relationships at the within-person level. As a result, the objective of this study was to investigate if within-person changes in perceived stress symptoms over a 1-month time period could predict injury rates during the subsequent 3 months. A prospective design with two measurement points (Time 1—at the beginning of the season and Time 2—1 month into the season) was utilized. A total of 121 competitive soccer players (85 males and 36 females; Mage = 18.39, SD = 3.08) from Sweden and the United States completed the Kessler Psychological Distress Scale (KPDS) and a demographic sheet at Time 1. The KPDS was also completed at Time 2, and all acute injuries that occurred during the subsequent 3-month period were recorded. A Bayesian latent change scores model was used to determine whether within-person changes in stress symptoms could predict the risk of injury. Results revealed that there was a credible positive effect of changes in stress symptoms on injury rates, indicating that an increase in reported stress symptoms was related to an increased risk for injury. This finding highlights the importance of creating caring and supportive sporting environments and relationships and teaching stress management techniques, especially during the earlier portion of competitive seasons, to possibly reduce the occurrence of injuries.